Raising awareness of climate change issues in Nigeria through education for policy and practice - Abdullahi, Nimota Jibola Kadir (Journal Of Research, Policy & Practice of Teachers & Teacher Education, 2020)
The objective of this study is to raise awareness through education in mitigating of climate issues. Also, to finding out relationship between resilience teaching and learning and mitigating of climate change issues in North-central zone, Nigeria. The study investigated managing education toward mitigating climate change in North-central zone, Nigeria. Stratified random sampling technique was used to select 375 head teachers and 384 teachers in public primary schools in North-central zone, Nigeria. Questionnaire title “Managing Education Toward Mitigating Climate Change Issues Questionnaire (METACCIQ) was used to collect data for the study and analysed using descriptive statistics and t-test analysis. The results shown that there is no significant difference between raising awareness, resilience teaching and learning and mitigating of climate change issues in Nigeria. It was recommended that Government, school administrators, teachers and stakeholders should embark on raising awareness on climate change issues to encourage changes in young people attitudes and behavior. Also, resilience teaching and learning should be made interesting in order to increases climate literacy among learners through education.
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change issues; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T14482 Innovations in Education Technology and Pedagogy; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found